STRATEGI OPTIMALISASI PENGELOLAAN DANA KAPITASI JAMINAN KESEHATAN NASIONAL PUSKESMAS DI KABUPATEN BONDOWOSO - Sari, Fitri Indah; Suroso, Imam; Nurhayati, Nurhayati (BISMA: Jurnal Bisnis dan Manajemen, 2017)
Abstract:The management of capitation funds of National Health Insurance (JKN) for the Regional Common Service Community Health Clinic is part of the regional financial management. The Public Health Service of Bondowoso Regency has implemented JKN since 2014. The capitation fund has a substantial excess funding with the increasing number of memberships and a management administration problem. This research aims to analyze the alternative strategy of optimizing the management of JKN capitation fund run by the Community Health Clinic in Bondowoso Regency using Strengths Weaknesess Opportunities and Threats (SWOT) analysis. The results of external and internal factor identification in Internal External (IE) matrix show that the value of External Factor Analysis Summary (EFAS) matrix is 2.96 and the value of External Factor Analysis Summary (IFAS) matrix value is 2.8. Accordingly, the strategic position for the Public Health Service is the hold and maintain position. Results of SWOT analysis show that there are 3 priority strategies, i.e., SO1 strategy (improving cooperation and cross sector coordination in technical management of the JKN capitation fund), SO2 strategy (improving monitoring and internal evaluation), and WO2 strategy (improving the manager’s competence by providing training and technical guidance). The most possible priority strategy based on the Quantitative Strategic Planning Matrix (QSPM) with the highest Total Attractiveness Score (TAS) of 6.117 is SO1 strategy, i.e., increasing cooperation and cross sector coordination in term of technical management of the JKN capitation fund. Keywords: Strategy, Financial Management, JKN.